Now is the time : Kunstmuseum Wolfsburg : The Collection - Beitin, Andreas; Broeker, Holger; Kunstmuseum Wolfsburg, Wolfsburg (Berlin : Hatje Cantz Verlag GmbH, 2019)
Ackermann, Franz ; Aiken, Doug ; Andre, Carl ; Araki, Nobuyoshi ; Arcangel, Cory ; Armleder, John M. ; Armstrong, Katie ; Artschwager, Richard ; Awst & Walther ; Bachmann, Caroline ; Banz, Stefan ; Báez, Firelei ; Baumgarten, Lothar ; Billingham, Richard ; Boltanski, Christian ; Brouwn, Stanley ; Chalayan, Hussein ; De Cock, Jan ; Cragg, Tony ; Daniëls, René ; Dibbets, Jan ; Doḡançay, Burhan ; Elíasson, Ólafur ; Federle, Helmut ; Fischli / Weiss ; Gamarra, Sandra ; Giehler, Torben ; Gilbert & George ; Gill, Gauri ; Gillick, Liam ; Gordon, Douglas ; Graham, Paul ; Gursky, Andreas ; Harte, Brian ; Havekost, Eberhard ; Hein, Jeppe ; Herold, Georg ; Hill, Gary ; Hirst, Damien ; Hofmann, Hanspeter ; Horn, Rebecca ; Hugo, Pieter ; Hume, Gary ; Immendorff, Jörg ; Jankowski, Christian ; Jensen, Sergej ; Kahrs, Johannes ; Keetman, Peter ; Kiefer, Anselm ; Kim, In Sook ; Knoebel, Imi ; Kocken, Gert Jan ; Kolehmainen, Ola ; Koons, Jeff ; Kounellis, Jannis ; Lebeck, Robert ; Leitolf, Eva ; Linz, Pia ; Lockhart, Sharon ; Majerus, Michel ; Marioni, Joseph ; Markowitsch, Rémy ; Mayer, Maix ; McCollum, Allan ; Mercier, Mathieu ; Merz, Gerhard ; Merz, Mario ; Milak, Radenko ; Morris, Sarah ; Nannucci, Maurizio ; Nauman, Bruce ; Opie, Julian ; Paik, Nam June ; Panamarenko ; Panton, Verner ; Pernice, Manfred ; Peyton, Elizabeth ; Pflumm, Daniel ; Piene, Otto ; Popp, Julius ; Potnis, Prajakta ; Rauch, Neo ; Rehberger, Tobias ; Ruthenbeck, Reiner ; Schütte, Thomas ; Sen, Mithu ; Sherman, Cindy ; Streuli, Beat ; Taaffe, Philip ; Tan, Fiona ; Taylor-Johnson, Sam ; Tronvoll, Mette ; Turrell, James ; Tuymans, Luc ; Vassileva, Mariana ; Wall, Jeff ; Weiner, Lawrence ; Welling, James ; Wolff, Tim ; Wurm, Erwin ; Zipp, Thomas
Now is the time, 25 Years Collection Kunstmuseum Wolfsburg, Wolfsburg, March 24 - September 29, 2019
boek